Privacy Information Security Classification for Internet of Things Based on Internet Data - Xiaofeng Lu; Zhaowei Qu; Qi Li; Pan Hui (International Journal of Distributed Sensor Networks)
A lot of privacy protection technologies have been proposed, but most of them are independent and aim at protecting some specific privacy. There is hardly enough deep study into the attributes of privacy. To minimize the damage and influence of the privacy disclosure, the important and sensitive privacy should be a priori preserved if all privacy pieces cannot be preserved. This paper focuses on studying the attributes of the privacy and proposes privacy information security classification (PISC) model. The privacy is classified into four security classifications by PISC, and each classification has its security goal, respectively. Google search engine is taken as the research platform to collect the related data for study. Based on the data from the search engine, we got the security classifications of 53 pieces of privacy.